The marine Tubificidae (Oligochaeta) of Hong Kong and Southern China - Erséus, C. (Asian Marine Biology, 1984)
Twenty-one estuarine and marine species of Tubificidae are reported from Hong Kong and the New Territories of Hong Kong. Taxonomic remarks and illustrations are provided for all species. Fourteen species that are new to science are described. Doliodrilus gen.n. (subfamily Limnodriloidinae) is established for the littoral, brackish-water species D. tener sp.n. Other new species are: Rhyacodrilus lutulentus, Bathydrilus edwardsi, Phallodrilus vanus, P. darvelli, Aktedrilus sinensis, A. mortoni, Bacescuella pilicrepus, Duridrius piger, Marcusaedrilus vesiculatus, Limnodriloides tenuiculus, L. toloensis, L. pictoni and L. fuscus. The ecology and distribution of the various species are briefly and preliminarily discussed. Some of the species found are identical, or very closely related, to forms known from Australia’s Great Barrier Reef. It is therefore concluded that the marine Tubificidae of southern China largely comprise elements of the tropical and subtropical fauna of the Indo-Pacific region.